Preparation method of neodymium-iron-boron magnet

By classifying, cleaning, coarsely crushing, and hydrogen-crushing processes of NdFeB magnet scraps, combined with air jet milling and additive mixing, new magnetic materials with qualified performance were prepared, solving the problem of recycling NdFeB magnet scraps and achieving efficient resource conversion and improved magnetic properties.

CN121306773APending Publication Date: 2026-01-09宁波金轮磁材技术有限公司
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511625524.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-07
Publication Date
2026-01-09

AI Technical Summary

Technical Problem

Existing technologies make it difficult to efficiently, economically, and environmentally recycle NdFeB magnet scraps, leading to a waste of rare earth resources and potential environmental threats.

Method used

Neodymium iron boron scraps are transformed into recyclable coarse powder through sorting, cleaning, coarse crushing and hydrogen crushing processes. Combined with fine treatment such as air jet milling and additive mixing, it is adapted to the new material. Finally, new magnetic materials with qualified performance are produced by magnetic field orientation molding and sintering.

Benefits of technology

This technology enables the efficient conversion and reuse of NdFeB scraps, avoids resource waste, improves magnetic properties and toughness, reduces raw material costs, and realizes the recycling of rare earth resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005676802720000061
    Figure BDA0005676802720000061
  • Figure BDA0005676802720000071
    Figure BDA0005676802720000071
  • Figure BDA0005676802720000072
    Figure BDA0005676802720000072
Patent Text Reader

Abstract

The invention relates to the field of neodymium-iron-boron magnet production processes, in particular to a neodymium-iron-boron magnet preparation method which comprises the following steps: S1, after neodymium-iron-boron leftover materials are classified, cleaned and coarsely crushed, hydrogen decrepitation is carried out, and recycled coarsely crushed powder B is obtained; s2, proportioning and smelting an alloy according to specified requirements, and carrying out hydrogen decrepitation to obtain new material coarsely crushed powder A; s3, after the powder A and the powder B are subjected to airflow milling, a lubricant, an antioxidant and aviation gasoline are added into the powder A and the powder B respectively, stirring and mixing are conducted, and fine powder A and fine powder B are obtained respectively; s4, the fine powder A and the fine powder B obtained in the S3 are mixed and sieved, and mixed powder C is obtained; and S5, the mixed powder C is subjected to magnetic field orientation forming, cooling static pressure, oil stripping and sintering, and finally the neodymium iron boron magnetic material is obtained. According to the method, efficient, economical and environment-friendly recycling of the neodymium-iron-boron magnetic material leftover materials is effectively achieved, and the neodymium-iron-boron magnetic material leftover materials are made into new magnetic materials with the performance reaching the standard again.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of neodymium iron boron magnet manufacturing processes, specifically to a method for preparing neodymium iron boron magnets. Background Technology

[0002] Neodymium iron boron (NdFeB) magnets are high-performance permanent magnet materials composed of elements such as neodymium (Nd), iron (Fe), and boron (B), and are known as the "King of Magnets." They possess extremely high magnetic energy product and coercivity, with magnetic properties far exceeding those of traditional magnets such as ferrite and AlNiCo. NdFeB magnets are small in size and light in weight, yet provide exceptionally strong magnetic force, and are widely used in high-tech fields such as new energy vehicle drive motors, wind turbines, consumer electronics (e.g., hard drives, headphones), medical devices, and industrial robots.

[0003] Neodymium iron boron (NdFeB) permanent magnets are a key basic material for modern high-tech industries, and their manufacturing mainly employs powder metallurgy sintering technology. During production, to meet the demands of products with different specifications and sizes, cutting, grinding, and other processing inevitably generate a large amount of scrap. Furthermore, the disposal of various end products also produces a considerable amount of waste magnets. These waste materials are rich in strategic rare earth elements such as neodymium, praseodymium, and dysprosium, representing a valuable secondary mineral resource. Directly discarding them would not only be a serious waste of scarce rare earth resources but could also pose a potential threat to the environment due to the heavy metals they contain. Summary of the Invention

[0004] In order to effectively solve the problem of efficient, economical and environmentally friendly recycling and reuse of neodymium iron boron magnet scraps, and to reprocess them into new magnets that meet performance standards.

[0005] This application provides a method for preparing neodymium iron boron magnets, using the following technical solution: A method for preparing a neodymium iron boron magnet includes the following steps: S1. After sorting, cleaning, and coarsely crushing the NdFeB scraps, hydrogen crushing is performed to obtain recycled coarse crushed powder B; S2. Prepare and melt the alloy according to the specified requirements, and obtain new coarse crushed powder A after hydrogen crushing; S3. After A powder and B powder are respectively subjected to air jet milling, lubricant, antioxidant and aviation gasoline are added to A powder and B powder respectively and stirred and mixed to obtain A fine powder and B fine powder respectively; S4. Mix the fine powder A obtained in S3 with the fine powder B and sieve to obtain mixed powder C; S5. The mixed powder C is subjected to magnetic field orientation molding, cooling and static pressing, oil stripping and sintering to finally obtain neodymium iron boron magnets.

[0006] Through the above technical solution, the waste neodymium iron boron scrap is first classified, cleaned, coarsely crushed and hydrogen crushed to be transformed into recyclable coarsely crushed powder B that can be reprocessed. Then, combined with fine treatment such as air jet milling and additive mixing, the scrap can be synergistically adapted with the new material A powder to the subsequent molding and sintering process, and finally it can be remade into new magnetic materials with qualified performance, realizing the efficient conversion and reuse of scrap resources and avoiding resource waste.

[0007] Preferably, in S3, before performing air jet milling, lubricant and aviation gasoline are added to the coarsely crushed powders of powder A and powder B and then stirred and mixed.

[0008] Through the above technical solution, the coarsely crushed powders A and B, after hydrogen crushing, retain trace amounts of minor oxides and oil stains on their surfaces. During high-speed collisions in the air jet mill, new active sites are generated. Adding lubricant at this stage can prevent grinding damage and adapt to high-efficiency grinding, thereby improving magnetic properties. Since lubricants are mostly solids or high-viscosity liquids, direct application makes uniform coverage difficult. Aviation gasoline can dissolve them into a homogeneous solution, which, after stirring, can coat the coarse powder.

[0009] Preferably, in S3, powder A is milled in an oxygenated environment, and powder B is milled in a non-oxygenated environment.

[0010] Through the above technical solution, powder A is a new material with high purity and strong particle activity after hydrogen crushing. During air jet milling, it is easy to generate a large number of submicron-sized ultrafine powders through high-speed collision. These ultrafine powders have extremely high specific surface area and surface energy. If they are not pre-oxygenated, they are more likely to oxidize and release heat in the subsequent molding stage. Once oxidation and heat release occur, the local temperature may rise, which may cause the surrounding normal-sized powders to oxidize as well, forming a potential trend of "ultrafine powder oxidation-heat release-chain oxidation". Ultimately, a certain amount of oxide impurities may appear in the mixed powder, thereby reducing the magnetic properties of the neodymium iron boron magnet.

[0011] Preferably, the oxygenation content in powder A is 60±10 PPM.

[0012] Through the above technical solution, when the oxygen content in powder A is too high, the excess oxygen will cause an excessively thick oxide layer to form on the surface of the powder with normal particle size, which is difficult to completely reduce during sintering. The residual oxide impurities (such as Nd2O3) will weaken the consistency of magnetic domain arrangement, resulting in a significant decrease in coercivity and remanence. When the oxygen content in powder A is too low, insufficient oxygen makes it difficult to completely passivate the activity of the ultrafine powder. The remaining high surface energy ultrafine powder will still be severely oxidized in subsequent molding, triggering a "chain oxidation" that destroys the magnetic properties of the neodymium iron boron magnet.

[0013] Preferably, in S4, the weight ratio of fine powder A to fine powder B in the mixed powder C is (5-7):(5-3).

[0014] With the above technical solution, when the proportion of fine powder A is high, the magnetic properties can be maximized, but the increase in the amount of new material will significantly increase the raw material cost, and the utilization rate of recycled material will decrease, which violates the original intention of "resource recycling" and loses the economic and environmental advantages.

[0015] When the proportion of fine powder A is low, the magnetic properties of recycled powder B are much lower than those of new powder A because recycled material B is made by remelting and remanufacturing scraps. When powder B becomes the main component, it will directly reduce the overall performance of the mixed powder, resulting in a decrease in the magnetic properties of the final magnet.

[0016] Preferably, the antioxidant is LaF3, and the amount of LaF3 added is 0.2-1 wt% of the total mass of the powder.

[0017] Through the above technical solution, LaF3 is selected as an antioxidant. Its melting point is much higher than that of NdFeB sintering temperature. It does not decompose or react with the main NdFeB phase during the entire preparation process. Moreover, LaF3 is inert only to the NdFeB main phase and conventional substances in the preparation process. It has a stronger tendency to react with "active impurities" such as oxygen and water on the surface of magnetic powder. It can preferentially react with these active impurities to form a dense LaF3 protective film, blocking the oxidation path from the source.

[0018] When the amount of LaF3 added is too low, it is difficult for LaF3 to form a continuous protective film. The magnetic powder is prone to contact with oxygen during storage and molding, which leads to an increase in oxygen content and a decrease in the magnetic properties of NdFeB. When the amount of LaF3 added is too high, the excess LaF3 will accumulate at the grain boundaries to form a brittle LaF3 phase, which weakens its ability to hinder crack propagation. The fracture toughness of the magnet will decrease, and it is prone to cracking during processing or use.

[0019] Preferably, the lubricant is zinc stearate, and the amount of zinc stearate added is 0.1-0.5 wt% of the total mass of the powder.

[0020] Through the above technical solution, zinc stearate molecules contain long-chain alkyl groups, which can form a directionally adsorbed lubricating film on the surface of magnetic powder, significantly reducing the friction coefficient between particles, effectively solving the agglomeration problem of fine powder after air jet milling due to its large specific surface area and strong van der Waals forces, and improving the flowability of powder.

[0021] When the amount of zinc stearate added is too low, it is difficult to form a complete lubricating film, resulting in high frictional resistance between magnetic powder particles. After air jet milling, the fine powder is prone to agglomeration, leading to uneven mold filling during magnetic field orientation molding, voids and delamination in the green body, which in turn leads to a decrease in the magnetic properties of the NdFeB magnet. When the amount of zinc stearate added is too high, the excess zinc stearate decomposes at the same time, making it difficult for CO2 to be completely discharged. Trace amounts of carbon are easily left behind, which react with the gas phase to form magnetic impurities, resulting in a decrease in coercivity and remanence.

[0022] Preferably, the aviation gasoline has a distillation range of 140-190°C.

[0023] With the above technical solution, when the distillation range of aviation gasoline is too low, the aviation gasoline is prone to premature evaporation at low temperature, causing the "additive-gasoline solution" before / after the air jet mill to dry out before the magnetic powder coating is completed. Zinc stearate and LaF3 are prone to agglomeration, making it difficult to uniformly cover the magnetic powder surface, losing the lubrication and anti-oxidation effects, resulting in a decrease in the magnetic properties of the neodymium iron boron magnet. When the distillation range of aviation gasoline is too high, it is difficult for the aviation gasoline to completely evaporate at the degreasing temperature of NdFeB, and hydrocarbon impurities are easily left behind. These impurities will carbonize during subsequent sintering, resulting in excessive carbon content in the magnetic powder, damaging the main phase NdFeB and causing a decrease in coercivity.

[0024] Preferably, in step S3, Mg powder is added to powder A and powder B together with lubricant, antioxidant and aviation gasoline.

[0025] Through the above technical solution, Mg powder, with its strong reducing properties, can preferentially react with FeO, Nd2O3 and other oxides remaining on the surface of magnetic powder to generate stable MgO. It can also form a dense "LaF3-MgO composite grain boundary phase" with LaF3, which can significantly block oxygen and water penetration to improve corrosion resistance. When the lubricant is zinc stearate, zinc stearate decomposes into ZnO during the degreasing stage. Mg powder diffuses directionally to the grain boundaries during sintering, refining the grain boundary phase grains. Furthermore, MgO and ZnO form a plastic "ZnO-MgO solid solution", which alleviates grain boundary stress and cracking tendency, and improves the fracture toughness of the magnet.

[0026] Preferably, the amount of Mg powder added in both powder A and powder B is 0.1-0.5 wt% of the total powder mass.

[0027] With the above technical solution, when the amount of Mg powder added is too low, the amount of Mg powder is too small to completely reduce the oxide on the surface of the magnetic powder, and it is also difficult to form a continuous "LaF3-MgO composite grain boundary phase", which leads to a decrease in corrosion resistance. At the same time, the Mg powder is insufficient to refine the grain boundary phase or form a sufficient amount of "ZnO-MgO solid solution", which leads to a decrease in the fracture toughness of the magnet.

[0028] When the amount of Mg powder added is too high, too much MgO accumulates at the grain boundaries, which exacerbates stress concentration and reduces the bending strength of the magnet.

[0029] In summary, this application has the following beneficial effects: 1. This application transforms waste NdFeB scrap into recyclable coarse crushed powder B through sorting, cleaning, coarse crushing, and hydrogen crushing processes. Then, combined with fine processing such as air jet milling and additive mixing, the scrap can be synergistically adapted with new material A powder for subsequent molding and sintering processes, and finally it can be remade into new magnetic materials with qualified performance, realizing the efficient conversion and reuse of scrap resources and avoiding resource waste. 2. This application selects LaF3 as an antioxidant, whose melting point is much higher than that of NdFeB sintering temperature. It does not decompose or react with the main NdFeB phase during the entire preparation process. Moreover, it has strong chemical inertness and can preferentially react with oxygen and water on the surface of magnetic powder to form a dense LaF3 protective film, thus blocking the oxidation path from the source. 3. In this application, Mg powder is added to powder A and powder B together with lubricant, antioxidant and aviation gasoline: Due to its strong reducing properties, Mg powder preferentially reacts with FeO and Nd2O3 on the surface of magnetic powder to form stable MgO, and also forms a dense composite grain boundary phase with LaF3 to block oxygen and water penetration to reduce salt spray weight loss rate; during sintering, Mg powder diffuses directionally to the grain boundary to refine the grains, and MgO and ZnO form a plastic solid solution to alleviate cracking tendency and improve the toughness and strength of the magnet. Detailed Implementation

[0030] The raw materials in this application include the following: Zinc stearate: Commercially available product with CAS number 557-05-1; LaF3: Lanthanum fluoride: Commercially available product with CAS number 20919-66-8; Aviation gasoline: Commercially available product with CAS number 86290-81-5; Mg powder: Magnesium powder: Commercially available product with CAS number 7439-95-4. Example 1 A method for preparing a neodymium iron boron magnet includes the following steps: S1. The NdFeB scraps are sorted and cleaned. 1000g of N33 NdFeB scrap and 1000g of N45 NdFeB scrap are weighed out, coarsely crushed, and then subjected to hydrogen crushing to obtain recovered coarse crushing powder B. The composition of coarse crushing powder B is determined to be: 18.74g of ferroborone, 220g of cerium, 5g of cobalt, 1.54g of copper, 1308.02g of iron, 420g of praseodymium-neodymium, and 3.0g of titanium. 8g, yttrium iron 16g, zirconium 4.54g, aluminum 3.08g; S2. According to the N45 neodymium iron boron magnet formula, the raw materials for the required A powder are calculated to be 28.26g of ferroborone, 220g of cerium, 10g of cobalt, 1984.58g of iron, 730g of praseodymium neodymium, 4.62g of titanium, 24g of yttrium iron, and 3.16g of zirconium. The above raw materials are weighed and hydrogen-crushed to obtain new coarse crushed powder A; S3. After grinding powder A and powder B into powders by air jet milling, add 9g of zinc stearate, 18g of LaF3 and 183mL of aviation gasoline with a distillation range of 150℃ to powder A and stir to mix to obtain fine powder A. Add 6g of zinc stearate, 12g of LaF3, and 122mL of aviation gasoline with a distillation range of 150℃ to powder B and stir to obtain fine powder B. S4. Mix 3000g of fine powder A with 2000g of fine powder B and sieve to obtain mixed powder C; S5. The mixed powder C is subjected to magnetic field orientation molding, cooling and static pressing, oil removal and sintering. The sintering temperature is 1110℃ and the sintering time is 3h to finally obtain neodymium iron boron magnet.

[0031] Example 2 Example 2: Based on the preparation method of Example 1, in S3, before air jet milling, 9g of zinc stearate and 183mL of aviation gasoline with a distillation range of 150℃ were added to powder A and stirred to obtain mixture A. Add 6g of zinc stearate and 122mL of aviation gasoline with a distillation range of 150℃ to powder B and stir to obtain mixture B.

[0032] Comparative Example 1 Comparative Example 1, based on the preparation method of Example 1, without S2, pulverized B powder by air jet milling, then added lubricant, antioxidant and aviation gasoline to B powder and stirred to obtain fine B powder; the fine B powder was then subjected to magnetic field orientation molding, cooling and static pressing, oil stripping and sintering to finally obtain neodymium iron boron magnet material.

[0033] The performance testing is as follows: The neodymium iron boron magnets of Examples 1-2 and Comparative Example 1 were analyzed, and the specific testing methods are as follows: Magnetic properties The intrinsic coercivity of permanent magnet (hard magnet) materials was tested according to GB / T3217-2013 "Magnetic Test Methods".

[0034] Based on the above detection method, the test results of Examples 1-3 and Comparative Example 1 were obtained, and the specific adjustments are shown in Table 1.

[0035] Table 1. Composition ratios and performance test data of neodymium iron boron magnets in Examples 1-2 and Comparative Example 1. project Example 1 Example 2 Comparative Example 1 Hcj / kOe 12.35 12.62 10.24 Referring to Table 1, it can be seen from the comparison between Example 2 and Example 1 that the magnetic properties of Example 2 are higher than those of Example 1. This is because the surface of the coarsely crushed powder A and powder B after hydrogen crushing treatment has residual tiny oxides and oil stains. During the high-speed collision of the air jet mill, new active sites will be generated. Adding lubricant at this stage can prevent grinding damage and adapt to efficient grinding, thereby improving the magnetic properties.

[0036] Comparing Example 1 and Comparative Example 1, it can be seen that the magnetic properties of Example 1 are much higher than those of Comparative Example 1. This is because Comparative Example 1 only uses recycled B powder, which has insufficient content of key elements such as praseodymium, neodymium, and cobalt, making it difficult to meet the high-performance requirements. In contrast, Example 1 uses a new material A powder prepared according to the N45 formula to compensate for the component defects of B powder, so that the key elements of the mixed A and B powders meet the standards. Moreover, both examples use precise additives according to quality, resulting in good molding and sintering properties of the mixed powder, which can generate a high-quality magnetic phase, thus leading to superior magnetic properties.

[0037] Examples 3-7 Example 3 is based on the preparation method of Example 1. In S3, powder A is subjected to air jet milling in an oxygenated environment with an oxygenation amount of 60 PPM, while powder B is subjected to air jet milling in an oxygen-free environment.

[0038] Examples 4-7 are based on the preparation method of Example 3, but the amount of oxygen added to powder A is adjusted, as shown in Table 2.

[0039] The neodymium iron boron magnets of Examples 1 and 3-7 were subjected to the above performance tests, and the test results are shown in Table 2.

[0040] Table 2. Oxygenation content and performance test data of powder A in Examples 1 and 3-7. project Example 1 Example 3 Example 4 Example 5 Example 6 Example 7 Oxygen dosage / PPM / 60 45 50 70 75 Hcj / kOe 12.35 13.83 12.57 13.14 13.32 12.71 Referring to Table 2, a comparison between Example 3 and Example 1 shows that the magnetic properties of Example 3 are higher than those of Example 1. This is because Powder A is a virgin material with high purity and strong particle activity after hydrogen crushing. During the air jet milling process, it easily generates a large amount of submicron-sized ultrafine powder through high-speed collision. This type of ultrafine powder has extremely high specific surface area and surface energy. If it is not pre-treated with oxygen, it is relatively likely to oxidize and release heat during the subsequent molding stage. Once oxidation and heat release occur, the local temperature may rise, which may in turn cause the surrounding powder of normal particle size to oxidize as well, forming a potential trend of "ultrafine powder oxidation → heat release → chain oxidation". Ultimately, this may result in a certain amount of oxide impurities in the mixed powder, thereby reducing the magnetic properties of the NdFeB magnet.

[0041] Comparative examples 3-7 show that both too low and too high oxygen content can lead to a decrease in the magnetic properties of NdFeB magnets. This is because when the oxygen content in powder A is too high, the excess oxygen will cause an excessively thick oxide layer to form on the surface of the powder with normal particle size, which is difficult to completely reduce during sintering. The residual oxide impurities (such as Nd2O3) will weaken the consistency of magnetic domain arrangement, resulting in a significant decrease in coercivity and remanence. When the oxygen content in powder A is too low, insufficient oxygen makes it difficult to completely passivate the activity of the ultrafine powder. The remaining high surface energy ultrafine powder will still be severely oxidized in subsequent molding, triggering a "chain oxidation" that leads to excessive oxygen content in the powder and damages the magnetic properties of the neodymium iron boron magnet.

[0042] Examples 8-11 Examples 8-11 are based on the preparation method of Example 1. In step S4, the weight ratio of fine powder A to fine powder B in the mixed powder C is adjusted as shown in Table 3.

[0043] The neodymium iron boron magnets of Examples 1 and 8-11 were subjected to the above performance tests, and the test results are shown in Table 3.

[0044] Table 3. Weight ratio and performance test data of fine powder A to fine powder B in Examples 1 and 8-11. Referring to Table 3, a comparison of Examples 8-11 and Example 1 shows that as the proportion of fine powder A increases, the corrosion resistance and magnetic properties of the magnetic material continuously improve. This is because the powder A is prepared according to the standard formula of high-performance N45 neodymium iron boron magnets, and the types and contents of its key components such as praseodymium, neodymium, cobalt, ferroboron, and titanium / yttrium iron all meet the formula requirements. Therefore, the fine powder A produced has a relatively low impurity content and its purity is more guaranteed. However, increasing the amount of virgin material significantly increases raw material costs and reduces the utilization rate of recycled materials.

[0045] Examples 12-15 Examples 12-15 are based on the preparation method of Example 1, but the amount of LaF3 added in S4 is adjusted, as shown in Table 4.

[0046] The neodymium iron boron magnets of Examples 1 and 12-15 were subjected to performance testing, and the test results are shown in Table 4.

[0047] toughness The magnet samples were processed into standard-sized impact specimens with a length of 55 mm and a cross-section of 10*10 mm, according to the "GB / T229-2007 Metallic Materials Charpy Pendulum Impact Test Method". The specimens had a V-shaped notch in the middle of the length, with an included angle of 45° and a depth of 2 mm. The impact toughness test was carried out using a JBS300 digital display pendulum impact testing machine with a 150J pendulum to obtain the absorbed energy of the magnetic material samples.

[0048] Table 4. Data on the addition amount and performance test results of LaF3 in powder A and powder B in Examples 1 and 12-15. Referring to Table 4, comparing Examples 12-15 with Example 1, it can be seen that when the LaF3 addition amount is too low, LaF3 is difficult to form a continuous protective film, and the magnetic powder is easily exposed to oxygen during storage and molding, leading to an increase in oxygen content and thus a decrease in the magnetic properties of the NdFeB magnet. When the LaF3 addition amount is too high, LaF3 itself is a non-magnetic compound, and excessive addition will form a large number of non-magnetic phases in the magnetic powder. These non-magnetic phases cannot participate in the formation of the NdFeB magnetic phase, but instead disperse between the magnetic phases like "impurity particles," disrupting the continuity of the magnetic phase. The directional arrangement of magnetic domains under the action of a magnetic field will be hindered by the non-magnetic phases, resulting in a decrease in the magnetic properties of the magnet.

[0049] Comparing Examples 12-15 with Example 1, it can be seen that when the LaF3 content is too high, excess LaF3 will accumulate at the grain boundaries to form a brittle LaF3 phase, which weakens its ability to hinder crack propagation and reduces the fracture toughness of the magnet, making it prone to cracking during processing or use. When the LaF3 content is too low, it is difficult to form a continuous protective film, and the magnetic powder is easily oxidized during storage and molding to generate oxide impurities. These oxides are usually hard and brittle, forming "mechanical weak points" inside the magnet. When the magnet is subjected to external force, cracks are prone to initiate at the interface between the oxide impurities and the matrix, and the oxides cannot buffer the stress, leading to rapid crack propagation and ultimately reducing the fracture toughness of the magnet.

[0050] Examples 16-19 Examples 16-19 are based on the preparation method of Example 1, but the amount of zinc stearate added in S4 is adjusted, as shown in Table 5.

[0051] The neodymium iron boron magnets of Examples 1 and 16-19 were subjected to the above performance tests, and the test results are shown in Table 5.

[0052] Table 5. Data on the addition amount and performance test results of zinc stearate in powder A and powder B in Examples 1 and 16-19. Referring to Table 5, comparing Examples 16-19 with Example 1, it can be seen that both too low and too high an amount of zinc stearate will lead to a decrease in the magnetic properties of NdFeB magnets. This is because when the amount of zinc stearate is too low, it is difficult to form a complete lubricating film, resulting in high frictional resistance between magnetic powder particles. After air jet milling, the fine powder is prone to agglomeration, leading to uneven mold filling during magnetic field orientation molding, voids and delamination in the green body, which in turn leads to a decrease in the magnetic properties of NdFeB magnets.

[0053] When the amount of zinc stearate added is too high, CO2 cannot be completely discharged when the excess zinc stearate decomposes, and trace amounts of carbon are easily left behind. The carbon will react with the main phase to form a magnetic impurity phase, which will lead to a decrease in the magnetic properties of the NdFeB magnet.

[0054] Examples 20-23 Examples 20-23 are based on the preparation method of Example 1, but in S4, the distillation range of aviation gasoline is adjusted, as shown in Table 6.

[0055] The neodymium iron boron magnets of Examples 1 and 20-23 were subjected to the above performance tests, and the test results are shown in Table 6.

[0056] Table 6. Distillation range and performance test data of aviation gasoline in Examples 1 and 20-23. Referring to Table 6, comparing Examples 20-23 and Example 1, it can be seen that both excessively low and excessively high distillation ranges of aviation gasoline can lead to a decrease in the magnetic properties of NdFeB magnets. This is because when the distillation range of aviation gasoline is too low, it is prone to premature evaporation at low temperatures, causing the "additive-gasoline solution" before and after the air jet mill to dry out before the magnetic powder coating is completed. Zinc stearate and LaF3 are prone to agglomerate into "clumps", making it difficult to uniformly cover the surface of the magnetic powder, resulting in a weakening of the lubrication and anti-oxidation effects, and thus a decrease in the magnetic properties of NdFeB magnets. When the distillation range of aviation gasoline is too high, the gasoline with the high distillation range is difficult to completely evaporate at the degreasing temperature of NdFeB, and hydrocarbon impurities are easily left behind. These impurities will carbonize during subsequent sintering, resulting in excessive carbon content in the magnetic powder, damaging the main phase NdFeB and causing a decrease in coercivity.

[0057] Examples 24-28 Example 24: Based on the preparation method of Example 1, in step S3, Mg powder, along with lubricant, antioxidant, and aviation gasoline, is added to powder A and powder B respectively. Specifically, 9g of Mg powder is added to powder A, and 6g of Mg powder is added to powder B.

[0058] Examples 25-28 are based on the preparation method of Example 23, but the amount of Mg powder added is adjusted, as shown in Table 7.

[0059] The neodymium iron boron magnets of Examples 1 and 24-28 were subjected to performance testing, and the test results are shown in Table 7.

[0060] Corrosion resistance A neutral salt spray test was conducted using a 5 wt% sodium chloride aqueous solution to spray the magnetic material samples at a temperature of 35°C. Since the corrosion reaction of NdFeB magnets in neutral salt spray is primarily oxidative exfoliation, the weight loss rate after 144 hours was used as the basis for assessing the corrosion resistance of the magnetic material samples. The 144-hour weight loss rate is calculated as: (mass before immersion - mass after immersion) / mass before immersion. Note: A lower weight loss rate indicates better corrosion resistance.

[0061] Table 7. Data on the addition amount of Mg powder in powder A and powder B in Examples 1 and 24-28, and related performance test results. Referring to Table 6, a comparison of Examples 24-28 and Example 1 shows that the corrosion resistance and toughness of Examples 24-28 are higher than those of Example 1. This is because Mg powder, with its strong reducing properties, can preferentially react with the oxides remaining on the surface of the magnetic powder to form stable compounds, and can also form a dense composite grain boundary phase with LaF3, significantly blocking oxygen and water penetration to improve corrosion resistance. During sintering, Mg powder diffuses directionally to the grain boundaries, refining the grain boundary phase grains. Furthermore, MgO and ZnO, the decomposition product of zinc stearate during the degreasing stage, form a plastic solid solution, alleviating grain boundary stress and cracking tendency, and improving the fracture toughness of the magnet.

[0062] Comparative examples 24-28 show that both excessively low and excessively high amounts of Mg powder can lead to a decrease in the corrosion resistance and fracture toughness of NdFeB magnets. This is because when the amount of Mg powder added is too low, a small amount of Mg powder is insufficient to form a sufficient amount of "LaF3-MgO composite grain boundary phase" and "ZnO-MgO solid solution" to block oxygen and water penetration, resulting in a decrease in corrosion resistance. Furthermore, the oxide impurities on the surface of the magnetic powder cannot be completely reduced, becoming weak points in toughness. At the same time, the grain boundaries lack buffer phases, and cracks tend to propagate rapidly under stress, leading to a decrease in the toughness of the magnet.

[0063] When the amount of Mg powder added is too high, the excess unreacted Mg accumulates at the grain boundaries in the form of elemental or low-valence oxides, which leads to uneven grain boundary structure, micropores or component segregation, forming a penetration path for corrosive media and causing a decline in corrosion resistance. Furthermore, the accumulation of oxides formed by excessive Mg at the grain boundaries or the formation of brittle intermetallic compounds with other elements can also cause uneven grain boundary structure, exacerbating stress concentration and becoming the starting point for crack initiation, making the magnetic material more prone to fracture under stress and reducing fracture toughness.

[0064] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A method for preparing a neodymium iron boron magnet, characterized in that, Includes the following steps: S1. After sorting, cleaning, and coarsely crushing the NdFeB scraps, hydrogen crushing is performed to obtain recycled coarse crushed powder B; S2. Prepare and melt the alloy according to the specified requirements, and obtain new coarse crushed powder A after hydrogen crushing; S3. After A powder and B powder are respectively subjected to air jet milling, lubricant, antioxidant and aviation gasoline are added to A powder and B powder respectively and stirred and mixed to obtain A fine powder and B fine powder respectively; S4. Mix fine powder A and fine powder B and sieve to obtain mixed powder C; S5. The mixed powder C is subjected to magnetic field orientation molding, cooling and static pressing, oil stripping and sintering to finally obtain neodymium iron boron magnets.

2. The method for preparing a neodymium iron boron magnet according to claim 1, characterized in that: In S3, before air jet milling, lubricant and aviation gasoline are added to the coarsely crushed powders of powder A and powder B and stirred and mixed.

3. The method for preparing a neodymium iron boron magnet according to claim 1, characterized in that: In S3, powder A is milled in an oxygenated environment, while powder B is milled in a non-oxygenated environment.

4. The method for preparing a neodymium iron boron magnet according to claim 3, characterized in that: The oxygenation content in powder A is 60±10PPM.

5. The method for preparing a neodymium iron boron magnet according to claim 1, characterized in that: In S4, the weight ratio of fine powder A to fine powder B in mixed powder C is (5-7):(5-3).

6. The method for preparing a neodymium iron boron magnet according to claim 1, characterized in that: The antioxidant is LaF3, and the amount of LaF3 added is 0.2-1 wt% of the total mass of the powder.

7. The method for preparing a neodymium iron boron magnet according to claim 1, characterized in that: The lubricant is zinc stearate, and the amount of zinc stearate added is 0.1-0.5 wt% of the total mass of the powder.

8. The method for preparing a neodymium iron boron magnet according to claim 2, characterized in that: The aviation gasoline has a distillation range of 140-190℃.

9. The method for preparing a neodymium iron boron magnet according to claim 1, characterized in that: In S3, Mg powder is added to powder A and powder B together with lubricant, antioxidant and aviation gasoline.

10. The method for preparing a neodymium iron boron magnet according to claim 9, characterized in that: In both powder A and powder B, the amount of Mg powder added is 0.1-0.5 wt% of the total powder mass.

Citation Information

Cited By

  • Integrated preparation method of low-attenuation neodymium-iron-boron magnet

    CN121790160A